Intera??o das ondas eletromagn?ticas com o material biol?gico - Scudeler, F?tima Clar?t S?da Ribeiro (2005)
ABSTRACT: "Interaction of the Electromagnetic Waves with the Biological Material" With the advance of the Telecommunications, the interaction between peopes, technology and machines, becomes very active, imperative and efficient, bringing as the final result one alone global community. This nwe technology that is very useful actually, becomes an essential integrant part of our life, it must to be understood as well as absorbed by the society, so that the persons can acquire the information how to usufruct of its benefits and in consequence learn to coexist with the negatives effects, that are certainly one minor priority. This dissertation presents a theoretical and numerical analysis on the performance of an incident wave over the human body. By taking into account the dielectric constants of some main parties of the body, that permit to represent a living being, are estimated the induced values of the electrical field as well as the specific absorption rate of the body. In this work is taken into consideration the communication systems used in the bandwidth of frequency adopted for the current mobile devices, and we make some comparisons with the international standards proposed by the ANATEL, as well as for a vast literature in this field of research. The approach presented here consider both thermal and non thermal effects due to the radiations, which study is complemented with real levels of measurements of radiations in order to check the conformity of the reached limits with the norms that would be accomplished in our Country. WORDS KEY: telecommunications; cellular mobile system; environment; not ionizing radiations; beings livings; amplitude of the signal.